2010
DOI: 10.3393/jksc.2010.26.6.407
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Clinical Features and Treatment for Right and Left Colonic Diverticulitis

Abstract: PurposeColonic diverticulitis is an uncommon disease in Korea, but the incidence of the disease is increasing. The right colon is the more preferred site for diverticulitis in Korea, but the incidence of left diverticulitis is increasing. Therefore, comparing the clinical features and treatments for right diverticulitis with those for left diverticulitis may help us to treat the disease more properly.MethodsThis study was performed retrospectively by reviewing the medical records of 96 patients with colonic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 14 publications
1
24
1
2
Order By: Relevance
“…The 8% prevalence of RCD is in accordance with that reported in literature [24,27,36]. For comparison, this percentage varies between 60-90% in Asians with acute diverticulitis [4,30].…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The 8% prevalence of RCD is in accordance with that reported in literature [24,27,36]. For comparison, this percentage varies between 60-90% in Asians with acute diverticulitis [4,30].…”
Section: Discussionsupporting
confidence: 79%
“…In addition, the recurrence rate of RCD of 7% in 7 years follow up in our study, is lower than that reported of LCD (up to 10-20% in 10 years) [4,11,18,33,[37][38][39].…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…This may be related to a higher intraluminal pressure in the right-side colon. Western people, mainly because of diet habits and constipation, form false diverticula in the left-sided colon (19). In this study, there were 10 cases of diverticulosis complicated with polyps, accounting for 23.8% of total patients with polyps.…”
Section: Wang Et Al a Contrastive Study Of Two Countries' Colonoscopmentioning
confidence: 90%